The Future of Children in the Criminal Justice System: Restorative or Retributive Approach - Widowati, Widowati (West Science Law and Human Rights, 2024)
The future of children within criminal justice systems raises fundamental questions about the best approach to both punishment and rehabilitation. This paper explores the competing paradigms of restorative and retributive justice, examining their impact on child offenders. Restorative justice focuses on rehabilitation, reconciliation, and reintegration into society, while retributive justice emphasizes punishment proportionate to the crime. Through an analysis of global case studies, legal frameworks, and criminological theories, this study assesses the effectiveness of each approach. It argues that restorative justice, though underutilized, offers more promising outcomes for reducing recidivism among child offenders, while retributive measures often fail to address the root causes of juvenile delinquency. The paper concludes by recommending a shift towards a more restorative model in juvenile justice systems, emphasizing the need for comprehensive policy reform to prioritize the long-term welfare of child offenders.